2020
DOI: 10.21273/hortsci14727-19
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate and Nutrient Uptake of Basil in Small-scale Hydroponics

Abstract: To identify practices that may simplify the use of small-scale hydroponic systems for indoor gardening, we compared two nutrient solution management treatments for basil (Ocimum basilicum) production. Experiments were conducted for 8 weeks to evaluate the effect of biweekly replacement of the nutrient solution (W) vs. biweekly fertilizer addition without nutrient solution replacement (W/O) on growth and nutrient uptake of basil ‘Genovese Compact’ grown in either a greenhouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Contradictions between nutrients concentrations in leaf tissue and solution were apparent and inconsistent with visual observations. Leaf tissue nutrient concentrations can be used to evaluate deficiencies [30,31]. In leaf tissue, nutrient concentrations in DAP+ did not differ or were less than DAP, but in solution, concentrations in DAP+ did not differ or were greater than DAP (Table 3, Figure 4).…”
Section: Adjustments To the Complemented Blendmentioning
confidence: 99%
“…Contradictions between nutrients concentrations in leaf tissue and solution were apparent and inconsistent with visual observations. Leaf tissue nutrient concentrations can be used to evaluate deficiencies [30,31]. In leaf tissue, nutrient concentrations in DAP+ did not differ or were less than DAP, but in solution, concentrations in DAP+ did not differ or were greater than DAP (Table 3, Figure 4).…”
Section: Adjustments To the Complemented Blendmentioning
confidence: 99%
“…In contrast, different management strategies could be used to minimize time, waste, and effort by home gardeners. In a study characterizing growth and nutrient uptake of hydroponically grown basil (Ocimum basilicum) in a greenhouse or indoors under solesource lighting, Solis-Toapanta et al (2020b) showed that within each environment, plants could be grown successfully for 8 weeks without a nutrient solution replacement. However, due to the limited plant growth indoors, excess nutrients accumulated in the solution when it was not consistently replaced.…”
Section: Unitsmentioning
confidence: 99%
“…Whereas plant growth is a function of environmental parameters, the effect there of is cumulative. It is expected that the plant develops best in optimal conditions of temperatures (Walters & Currey, 2019), with optimal light concentrations (Solis-Toapanta & Gomez, 2019), with optimal water consumption and nutrient availability (Solis-Toapanta et al, 2020). When the system becomes stressed, whether, because of high temperatures or depleted soils, with low contents of organic matter, and therefore, low water storage capacity, the RGR values are low.…”
Section: Discussionmentioning
confidence: 99%